A SYSTEMIC FUNCTIONAL LINGUISTICS (SFL) ANALYSIS OF EXPOSITION TEXTS AS TEACHING MATERIALS WRITTEN BY PRE-SERVICE TEACHERS - R. Winda Herdisa Dewi (Journal of English and Education, 2016)
The research is entitled A Systemic Functional Linguistics (SFL) Analysis of Exposition Texts as Teaching Materials Written by Pre-Service Teachers. This research aims at observing the teachers’ Subject Matter Knowledge competence by analyzing the coherence of analytical exposition texts written by three English pre- service teachers in a senior high school in terms of their schematic structure and theme system. To accomplish this aim, a qualitative research study design involving text analysis and interviews was conducted. It is found out that the pre-service teachers were able to make coherent text seen from Theme and Thematic Progression. Meanwhile, the results from interviews showed that they encountered the challenges. The first challenge was to make the text more relevant and coherent. That is, the main argument must be supported by the arguments which were written by the pre-service teachers. The second challenge was to distinguish between censorship and professional. Based on five categories as proposed by National Council of Teacher of English (2014), there was one category which could not be fulfilled by one pre-service teacher. From the analysis of interview, nonetheless the texts written by pre-service teachers seemed to generally reflect